A new voltammetric approach for the determination of the growth retardant paclobutrazol in the presence of difenoconazole in pesticide preparations - Jiroutová, Alona; Chýlková, Jaromíra; Váňa, Jiří; Matvieiev, Oleksandr; Janíková, Lenka; Šelešovská, Renáta (Elsevier Science SA, 2023)
Paclobutrazol (PBZ) belongs to the group of triazole pesticides, which act as inhibitors of the synthesis of phy-tohormones and thereby regulate plant growth. In this study, the electrochemical oxidation of this pesticide was investigated for the first time. PBZ provides on a boron-doped diamond electrode (BDDE) one irreversible anodic peak over a wide pH range of the supporting electrolyte at a significantly positive potential of ca. +1950 mV (vs Ag/AgCl), which is suitable for electroanalytical purposes. Based on the LC-MS analysis of the products of electrolysis, the mechanism of the electrochemical oxidation of PBZ was also proposed. The method developed for the determination of PBZ using differential pulse voltammetry in connection with BDDE in the supporting electrolyte of 0.07 mol L-1 NaOH with 33 % of acetonitrile provided a very low limit of quantification amounted to 2.6 x 10-7 mol L-1. Under optimized conditions, the determination of the stud-ied plant growth regulator is also possible in the presence of the other insecticide difenoconazole, which is usu-ally found in commercial preparations mixed with PBZ. For natural water samples with very low concentrations of pesticides, a method of analyte pre-concentration using strong acid Amberlite (R) IRC120 H catex was developed. The proposed procedures were successfully applied for the analysis of model solutions, commercially available pesticide preparations, and spiked natural waters.
Nový voltametrický přístup ke stanovení růstového regulátoru paclobutrazolu v přítomnosti difenokonazolu v pesticidních přípravcích
Keywords: Paclobutrazol; Difenoconazole; Oxidation; Voltammetric determination; Boron-doped diamond electrode; Pre-concentration procedure; Paclobutrazol; Difenoconazol; Oxidace; Voltametrické stanovení; Borem dopovaná diamantová elektroda; pre-koncentrační procedura